Pengaruh Latihan Footwork Dan Latihan Skipping Terhadap Ketepatan Forehand Smash Pada Atlet Bulutangkis Pb.Patriot Sidoarjo - Amirrudin Amirrudin; Rufi’i Rufi’i; Abd Cholid (UNIVERSITAS NEGERI MAKASSSAR, 2021)
This study aims to determine the effect of footwork and skipping exercises on the accuracy of badminton forehand smashes. In this study, it is easier for athletes to learn to perform the precision of the forehand smash in PB. PATRIOT Simowau Sidoarjo. Researchers chose footwork and skipping exercises because in this exercise the focus was on leg movements and agility on the forehand smash. This research is a quantitative approach and type of experimental research, which is to look for the effect of footwork and Skipping exercises on the accuracy of forehend smashes on athletes. The results of this study indicate that, there is no difference between the accuracy of the forehand smash between footwork and skipping exercises, it can be concluded that Ho is accepted and Ha is rejected because the Fcount value <Ftable, or 0.159 <4.49. It can be proven through the probability sig = 0.695 and α = 0.05 or Hence sig> α, or 0.695> 0.05. In the accuracy of the forehand smash between high and low initial knowledge in athletes, no difference can be concluded that Ho is accepted and Ha is rejected because the Fcount <Ftable, or 3.372 <4.49. It can be proven through probability sig = 0.085, and α = 0.05 or Hence sig> α, or 0.085> 0.05. In the interaction of footwork and skipping exercises and initial knowledge of the accuracy of the forehand smash in athletes there is an interaction it can be concluded that Ho is accepted and Ha is rejected because the value of Fcount> Ftable, or 4.647> 4.49. Can be proven through the probability of sig = 0.085, and α = 0.05 or Hence sig <α, or 0.047 <0.05.